2009
DOI: 10.1111/j.1365-2702.2009.02795.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to nursing task incompletion as perceived by nurses working in Kuwait general hospitals

Abstract: Emphasis should be given to maintaining the optimum nurse-patient load and decreasing the non-nursing workload of nurses to enhance the quality of nursing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(126 citation statements)
references
References 19 publications
7
116
1
2
Order By: Relevance
“…This finding is consistent with prior research. [7–9, 1, 21] Uniquely, this study also estimated the impact of subscales of the PES-NWI, including the dimension of staffing and resource adequacy in separate models, thus extending our knowledge on the specific factors that were associated with missed nursing care. We found that the nursing practice environment, as measured by the composite PES-NWI and subscales, explained 22–60% of the variance in missed nursing care.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with prior research. [7–9, 1, 21] Uniquely, this study also estimated the impact of subscales of the PES-NWI, including the dimension of staffing and resource adequacy in separate models, thus extending our knowledge on the specific factors that were associated with missed nursing care. We found that the nursing practice environment, as measured by the composite PES-NWI and subscales, explained 22–60% of the variance in missed nursing care.…”
Section: Discussionmentioning
confidence: 91%
“…Missed nursing care was measured using a composite score on a measure referred to as “Tasks Left Undone,” a scale developed by Lucero and colleagues and used in other high impact research [7, 21] This is a 12- item scale that asks nurses to identify patient care activities on their last shift that they thought were necessary, but left undone. The scale construct validity has been demonstrated by other studies that found it is associated in the theoretically expected direction with RN staffing, quality of care, and frequency of adverse events in hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…It is plausible that the different time frames provide some explanation of the differences in missed care or rationing level between the North American (Kalisch et al ., ; Gravlin and Bittner, ) and European studies (Schubert et al ., , ), as self‐reported rationing in the latter group was lower. Eight studies reported elements of care being rationed and the causes of rationing (Morin and Leblanc, ; Al‐Kandari and Thomas, ; Kalisch et al ., ; Lucero et al ., ; Gravlin and Bittner, ; Rochefort and Clarke, ; Kalisch et al ., ), six studies reported significant correlations between nursing care rationing and patient outcomes (Sochalski, , Schubert et al ., ; Schubert et al ., ; Lucero et al ., ; Kalisch et al ., ; Schubert et al ., ) and three studies have correlated nursing care rationing with nurse job outcomes (Lucero et al ., ; Tschannen et al ., ; Kalisch et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…While several studies explore the negative public perceptions of nurses (Al-Kandari & Thomas, 2009;Lovering, 2008;Nasrabadi et al, 2004;Wehbe-Alamah, 2008), none were found that also revealed the added perception of feeling disrespected in the eyes of global public opinion for being Muslim. "Most of the nurses here .…”
Section: Primary Themesmentioning
confidence: 99%